Advantages and disadvantages of Raman spectroscopy in testing paper banknotes - Jauković, Gordana (Array, 2019)
This paper presents advantages and disadvantages of Raman spectroscopy when used for testing banknotes, i.e. in case study I, 1 and 5 dinars banknotes from a private collection dating from 1876 of numismatic value were analyzed, and in case study II, 1000 dinars banknote from circulation together with its counterfeit. In both cases banknotes were analyzed by using Raman spectrometer DXR Raman microscope at the Faculty of Physical Chemistry, with a laser of wave-length 780 nm at 12 mW of power. Specters were recorded under microscope using 50X lens in a range 1800-60 cm-1. Analyses from case study I on both specimens showed spectrum characteristic for fluorescence appearance, therefore intensive signal of fluorescence covered Raman signal. In case study II, it was established that Raman spectroscopy can reliably detect a counterfeit banknote. Research, comparisons and analyses regarding original and counterfeit 1000 dinars note were performed on red banknote surfaces.